AAPM recommendations on medical physics practices for ocular plaque brachytherapy: Report of task group 221. Issue 5 (18th March 2020) - Thomson, Rowan M.; Furutani, Keith M.; Kaulich, Theodor W.; Mourtada, Firas; Rivard, Mark J.; Soares, Christopher G.; Vanneste, Françoise M.; Melhus, Christopher S.
Abstract : The American Association of Physicists in Medicine (AAPM) formed Task Group 221 (TG‐221) to discuss a generalized commissioning process, quality management considerations, and clinical physics practice standards for ocular plaque brachytherapy. The purpose of this report is also, in part, to aid the clinician to implement recommendations of the AAPM TG‐129 report, which placed emphasis on dosimetric considerations for ocular brachytherapy applicators used in the Collaborative Ocular Melanoma Study (COMS). This report is intended to assist medical physicists in establishing a new ocular brachytherapy program and, for existing programs, in reviewing and updating clinical practices. The report scope includes photon‐ and beta‐emitting sources and source:applicator combinations. Dosimetric studies for photon and beta sources are reviewed to summarize the salient issues and provide references for additional study. The components of an ocular plaque brachytherapy quality management program are discussed, including radiation safety considerations, source calibration methodology, applicator commissioning, imaging quality assurance tests for treatment planning, treatment planning strategies, and treatment planning system commissioning. Finally, specific guidelines for commissioning an ocular plaque brachytherapy program, clinical physics practice standards in ocular plaque brachytherapy, and other areas reflecting the need for specialized treatment planning systems, measurement phantoms, and detectors (among other topics) to support the clinical practice of ocular brachytherapy are presented. Expected future advances and developments for ocular brachytherapy are discussed.